A Intercompreensão em Didática de Línguas : modulações em torno de uma abordagem interacional - Sá, Maria Helena Araújo e (Linguarum Arena, 2018)
Intercomprehension (IC) is a structuring and sustaining concept of current plural approaches in Language Didactics (LD) and also one of the most dynamic in recent discourses and practices of this disciplinary area. Addressed by several voices, more or less harmonious, according to authors and their schools’s epistemological belongings, IC has been tackled according to several perspectives that instead of contributing to its theoretical disaggregation, have been promoting multiple approximation and convergence movements between didacticians. These movements are supported by studies that, adopting different methodologies, aim at delimiting the concept and thus building a shared support base from which each author and group can make their choices, defining and differentiating their ways and contributing collectively to the notion dynamics. In this paper, after an initial stage within which I try to quickly characterize the diversity of possible paths in intercomprehension, or the polyphony of this “meta-concept”, I focus on one of the possible approaches that I have been practicing, the interactional one, explaining its anchors within the specific field of LD and illustrating it with a concrete teaching resource: the Galanet platform.